Study on the physical capacity development for the handball player, junior II, item of the specialized as backcourt - Tohanean, D.; Talaghir, L.-G. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2016)
The research is exploratory and descriptive study, whose target population a total of 30 athletes, practitioners of the handball game, members of the junior level II (15-16 years old) - men's 6 teams. Subjects were randomly assigned into 2 groups (experimental and control) by 15 athletes. The overall conclusion of this study is that specific physical capacity through specific physical training leads to an improvement index, which is the medium in which further enhance technical and tactical skills.